2004
DOI: 10.3168/jds.s0022-0302(04)73421-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pasture Allowance and Supplementation on Feed Efficiency and Profitability of Dairy Systems

Abstract: Partial budgeting was used to compare income over feed costs of high-yielding Holstein cows based on data from an experiment with 4 dietary treatments arranged in a 2 x 2 factorial. The factors were low (25 kg DM/cow per day) and high (40 kg DM/cow per day) pasture allowance (PA) and supplemental grain fed at 1 kg/4 kg of milk or no supplemental grain fed. The 4 treatments were low PA unsupplemented (LPAU), low PA concentrate supplementation (LPAC), high PA unsupplemented (HPAU), and high PA concentrate supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
(25 reference statements)
2
15
0
1
Order By: Relevance
“…Thus, lower intakes at the higher stocking rates were avoided, removing one of the main causes of poor FCE in pasture‐based systems (Beever and Doyle, 2007; Kolver, 2007). These results are in line with those by Tozer et al. (2004) who also found no effect of increasing stocking rate on FCE working with high genetic merit cows on supplemented pasture‐based systems.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, lower intakes at the higher stocking rates were avoided, removing one of the main causes of poor FCE in pasture‐based systems (Beever and Doyle, 2007; Kolver, 2007). These results are in line with those by Tozer et al. (2004) who also found no effect of increasing stocking rate on FCE working with high genetic merit cows on supplemented pasture‐based systems.…”
Section: Discussionsupporting
confidence: 91%
“…, 2009) proposed that with improved feeding management (i.e. including supplementation when pasture availability is limiting), farmers could avoid reductions in feed intake and milk yield per cow and therefore in FCE (Tozer et al. , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency of supplementation depends on the relative costs of grazing and supplement, grazed herbage allowance, season and stage of lactation (Tozer, Bargo, & Muller, 2004). Although herbage DMI is reduced, total DMI is increased and the reduction in total N intake is inversely related to substitution rate.…”
Section: Efficiency Of Nitrogen Usementioning
confidence: 99%
“…Calculating the income over feed costs, Tozer et al (2004) found a better performance in Supplemented cows ($4.51 vs. $3.30/cow/day). Numerous studies have examined production responses to concentrates in cows of medium or high milk potential consuming tropical forages, but reproductive variables have not been reported (Combellas, 1998).…”
Section: Introductionmentioning
confidence: 96%